Kualitas silase rumput gajah yang diberi tepung umbi talas sebagai aditif silase - Ria Anjalani; Lisnawaty Silitonga; Maria Haryulin Astuti (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This study was conducted to obtain the effects of taro corm meal addition level on quality of elephant grass silage. There were four levels of taro corm meal (DM basis) i.e. 0% (control), 5% (P1), 10% (P2), and 15% (P3) (w/w). Each treatments consisted of 5 replications. Silage were placed in plastic bags as silo. This study was designed in Completely Randomized Design. The observation conducted to physical quality and chemical composition of silage. The physical quality of silage were color, odor, texture, and growth of fungi. Chemical composition of silage consisted of dry matter (DM), organic matter (OM), crude protein (CP), crude fiber (CF), extract ether (EE), and Nitrogen Free Extract (NFE). The study showed that silage from P0, P1, P2, and P3 had brownish green color, acid odor, non-sticky texture, and no fungus found. The addition of taro corm meal significantly affected DM, OM, CP, CF, EE, and NFE content of elephant grass silage (P